An analysis of the support and quality of live after the diagnosis and treatment of prostate cancer in the radiotherapy sector (Brazilian Journal of Radiation Sciences, 2021)
Prostate cancer is the most common chronic disease among men in most parts of the world. According to the National Cancer Institute (INCA) in Brazil in 2018, 68,000 new cases were registered. Among the main treatments the radiotherapy has been shown to be effective in controlling and curing the disease. However, it is noted that the patient satisfaction index is not the most encouraging and there is little research that points to the sup-port of the hospital team. The aim of this study was to collect data from medical records about the adverse effect of the disease and through questionnaire the level of knowledge about the disease and the support offered by sector and to make recommendations for radiotherapy units Data were collected from 147 patients and of that total, 51 answered the questionnaire. The survey also shows that there was little referral to the complementary therapeutic service during of treatment. It is identified that more than 50% them knew very little about prostate cancer and 42% had no participation in the choice of treatment. It is observed that it is difficult to insert support policies for patients with prostate cancer, the professionals who work in oncology and radiotherapy centers underestimate the effects of the disease. It is observed, through research, that many of the symptoms and debilitations could be mitigated if there was a greater interaction between the health team and the patient, reducing the effects of radiation and accelerating the patient's integration for the social environment.
Keywords: radiotherapy 1; support 2; quality of life 3; prostate cancer 4